Message Analysis Between Agents for Detection of Emerging Behaviors in Open Environments - Castello, Rodolfo; Ventura, Carlos (Advances in Practical Applications of Cyber-Physical Multi-Agent Systems: The PAAMS Collection, 2017)
Emerging multi-agent behaviors are explained as conducts that appear during run-time in multi agent software applications [1]. These categories of actions are not detected at the validation and verification stages. Proposals such as architectures, patterns for their detection and metrics have been presented and so far, more research is required in this area [2, 3]. The demonstration in this document proposes to visually find the patterns exhibited by agent communication in a visually analyzable and traceable format.